1984
DOI: 10.1104/pp.75.4.1090
|View full text |Cite
|
Sign up to set email alerts
|

Does Pollination Induce Corolla Abscission of Cyclamen Flowers by Promoting Ethylene Production?

Abstract: AUSTRACF MATERIALS AND METHODSVery low ethylee production rates were measured in nonpoilinated Cyclame persum Mill flows, aod o change in production was observed dring the whoie lfe spa of the flower until death. Normal senscence was accompnd by a gradul discolotion aod loss of turgor followed by wilting. Polliation induced a dramatic i emin ethylene evoluon, culmatg in a peak 4 days after pollinatio, and a of the corolla on that day. Silver-thioslfate, an inhibitor of ethylene acton, had no effect on longevit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…It may therefore be concluded that the transported signal is not ACC but, rather, ethylene itself may be translocated or the lip may become more sensitive to ethylene following emasculation. The latter would meet our expectations as the existence of (mobile) ethylene-sensitivity factor(s) has also been suggested in cyclamen, petunia, and carnation flowers (7,9,13,19).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It may therefore be concluded that the transported signal is not ACC but, rather, ethylene itself may be translocated or the lip may become more sensitive to ethylene following emasculation. The latter would meet our expectations as the existence of (mobile) ethylene-sensitivity factor(s) has also been suggested in cyclamen, petunia, and carnation flowers (7,9,13,19).…”
Section: Discussionsupporting
confidence: 62%
“…decanoic acid and octanoic acid, were isolated from eluates of pollinated Petunia styles (19). In Cyclamen flowers, pollination-induced corolla abscission was ascribed to the action of a pollination-induced ethylene-sensitivity factor as abscission in pollinated flowers could be prevented by silver thiosulphate whereas it could not be induced by ethylene or ACC in nonpollinated flowers (7). Similarly, such a mobile ethylene-sensitivity factor was suggested to be produced in the lower portion of the carnation petal (13).…”
mentioning
confidence: 99%
“…Ethylene production by AOA-treated petals was not detected (level of sensitivity : 0.010 1u/L) throughout the 32-h experiment (Fig. 3) 10 Ml/L ethylene as described under "Materials and Methods." After 2 h, petals were transferred to distilled H20 for the remainder of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of flowers to ethylene varies greatly among plant species (9,10). In general, there is a gradual increase in the flower's sensitivity to ethylene with increasing age (5, 9, 13, 18).…”
mentioning
confidence: 99%
“…The effect of pollination can be blocked by treatment with ethylene action inhibitors, and exogenous ethylene treatment accelerates senescence in these flowers. Flowers of other plants such as cyclamen senesce in response to ethylene only when pollinated (Halevy et al, 1984). It should be noted here that patterns of petal senescence can vary even within species but are specific to cultivars.…”
Section: Introductionmentioning
confidence: 99%